2011
DOI: 10.1037/a0023213
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between informant and self-reported personality in depressed older adults: What are the roles of medical illness and cognitive function?

Abstract: In a sample of 77 dyads, involving depressed patients at least 50 years of age and their family or friends (informants), patient illness burden and cognitive decline were associated with selfinformant rating discrepancies for facets of NEO-PI-R Openness and Extraversion. Informant judgments about Neuroticism and Conscientiousness were not associated with illness burden or cognitive function, underscoring the potential utility of risk-detection strategies that rely on informant-report in these two domains. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…This is unlikely, however, given the generally consistent worldwide rates of psychiatric diagnoses assessed postmortem and the frequent presence of corroborating medical documentation before death. With respect to the accuracy of informant reports, much has been learned over the past decade about the capacity of informants to provide accurate data about the internal state of another person (Funder, 1995;Hoerger et al, 2011). For example, it has been shown that informants are likely to underestimate the extent to which a target experiences positive emotions and overestimate self-consciousness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is unlikely, however, given the generally consistent worldwide rates of psychiatric diagnoses assessed postmortem and the frequent presence of corroborating medical documentation before death. With respect to the accuracy of informant reports, much has been learned over the past decade about the capacity of informants to provide accurate data about the internal state of another person (Funder, 1995;Hoerger et al, 2011). For example, it has been shown that informants are likely to underestimate the extent to which a target experiences positive emotions and overestimate self-consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that informants are likely to underestimate the extent to which a target experiences positive emotions and overestimate self-consciousness. Some of these discrepancies can be ascribed in part to the target's level of cognitive function or medical burden (Hoerger et al, 2011); although we statistically adjusted for medical burden, data on cognitive function were unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive difficulties of the participant may lead to larger discrepancies because participants and proxies may not communicate as efficiently as they may have done in the past (Reamy et al, 2011). Poor health may also serve as a risk factor for incongruence because health impairments compromise the quality of information available to the proxy (see Funder, 2003;Hoerger et al, 2011;Sneeuw et al, 1998). We also evaluate the extent to which characteristics of the proxy moderate congruence.…”
Section: Congruence Between Proxy and Self-reports Of Life Satisfactionmentioning
confidence: 99%
“…Importantly, prior research suggests that self-reported Openness is more strongly associated with cognitive functioning than informant reports (Hoerger et al, 2011), suggesting that self-reports of Openness might be more sensitive to incipient decline than informant reports. As described in Suchy et al (2011), two screenings of cognitive status approximately one year apart were conducted in a sample of older adults.…”
Section: Introductionmentioning
confidence: 98%